A Model of Successful Local Governance in Ethnically Diverse Highland Communities: A Case Study of Ban Luang Subdistrict Municipality, Chom Thong District, Chiang Mai Province - Kantaros, Nattapong; Santivong, Amarita; Settakorn, Wit; Metasuttirat, Jirawat (Journal of Public Administration Chiang Rai Rajabhat University, 2026)
The objectives of this research article are: (1) To study and analyze the key success factors in local governance within ethnically diverse highland areas of Ban Luang Subdistrict Municipality, Chom Thong District, Chiang Mai Province, and (2) To propose a model of successful local governance in ethnically diverse highland areas of Ban Luang Subdistrict Municipality, Chom Thong District, Chiang Mai, The study employed a qualitative case study design, incorporating in-depth interviews and focus group discussions. Data were collected from 25 participants, including municipal executives, council members, municipal officials, stakeholders, and representatives from local networks. Semi-structured interview and focus group protocols were used as research instruments. The data were analyzed and interpreted using content analysis, and methodological triangulation was employed to ensure validity and reliability through comparisons of data from document analysis, interviews, and focus group discussions. The findings reveal four key success factors for local governance in Ban Luang’s ethnically diverse highland setting: (1) strong teamwork and collaborative operations; (2) a cohesive organizational culture; (3) active community and local authority participation; and (4) support from local and ethnic networks. Building on these results, the study proposes a model of successful local governance comprising: (1) leadership as a pivotal driver; (2) effective organization and administration; (3) robust networking; and (4) broad-based collaboration and public participation. However, persistent challenges remain, including legal and regulatory constraints, budgetary limitations, and shortages of human resources. The study recommends strengthening engagement with local agencies and advancing multi-sectoral partnerships to consolidate cooperative and participatory governance.